2022
DOI: 10.3390/ijms23158146
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA Signature for the Diagnosis of Statins Intolerance

Abstract: Atherosclerotic cardiovascular diseases (ASCVD) are the leading cause of morbidity and mortality in Western societies. Statins are the first-choice therapy for dislipidemias and are considered the cornerstone of ASCVD. Statin-associated muscle symptoms are the main reason for dropout of this treatment. There is an urgent need to identify new biomarkers with discriminative precision for diagnosing intolerance to statins (SI) in patients. MicroRNAs (miRNAs) have emerged as evolutionarily conserved molecules that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…MiRNAs in circulation have been shown to indicate the status of thrombocytes in real time and that they can be used as biomarkers for the prediction of various aspects of their function, i.e., they can be used for monitoring and adjusting anti-aggregation therapy [ 46 , 47 ]. Additionally, it has been confirmed that miRNAs affect anticoagulation therapy with coumarin derivatives [ 48 ], therapy with direct anticoagulation drugs [ 49 ], and that they also affect therapy with statins, i.e., statin intolerance [ 50 ]. The predictive potential of long non-coding RNAs has also been recognised for the effects of anti-aggregation therapy [ 51 ].…”
Section: Molecular Biology As a Promoter Of Research And Treatment Of...mentioning
confidence: 99%
“…MiRNAs in circulation have been shown to indicate the status of thrombocytes in real time and that they can be used as biomarkers for the prediction of various aspects of their function, i.e., they can be used for monitoring and adjusting anti-aggregation therapy [ 46 , 47 ]. Additionally, it has been confirmed that miRNAs affect anticoagulation therapy with coumarin derivatives [ 48 ], therapy with direct anticoagulation drugs [ 49 ], and that they also affect therapy with statins, i.e., statin intolerance [ 50 ]. The predictive potential of long non-coding RNAs has also been recognised for the effects of anti-aggregation therapy [ 51 ].…”
Section: Molecular Biology As a Promoter Of Research And Treatment Of...mentioning
confidence: 99%
“…Therefore, it is important to distinguish patients with statin intolerance before they present muscle symptoms. Mangas et al [ 10 ] identified a new microRNA signature capable of discriminating between statin-intolerant and non-statin-intolerant patients. Moreover, when the authors add clinical information, such as years of dyslipidemia or non-high-density cholesterol levels, this set of circulating miRNAs significantly increases in accuracy.…”
mentioning
confidence: 99%